MC12: An opportunity to find an enduring solution on public stockholding - Sinha, Tanvi; Glauber, Joseph W. (International Institute for Sustainable Development, 2021)
Public stockholding programs are essential for food security but can present various problems for many developing countries. Tanvi Sinha from The Commonwealth and Joe Glauber from the International Food Research Institute present five options that could help negotiators find a long-lasting solution.